Prior Knowledge of Diagnostic Results Does Not Bias A Subject’s Interpretation of At-Home COVID-19 Antigen Tests - Lai, Eric (COVID, 2023)
In developing in vitro diagnostic (IVD) tests, in particular at-home/over-the-counter (OTC) tests, one of the generally accepted exclusion criteria in IVD clinical trial protocols has been that of subjects with prior knowledge of their positive status, due to potential bias. With COVID-19 antigen tests now widely available, it is common for individuals to test themselves at home with an antigen test if they have symptoms associated with COVID-19, flu, or the common cold. These subjects would be excluded from participation in COVID-19-related clinical trials (i.e., COVID-19 alone or any multiplex tests that include COVID-19). This study compiled the results of four clinical trials to assesses whether potential bias (positive or negative) exists in at-home antigen COVID-19 testing if someone has a prior diagnostic COVID-19 result. The results clearly demonstrated that knowledge of prior COVID-19 diagnostic results did not affect the accuracy of the test result interpretations nor the clinical performance of the at-home antigen test products. This is an important finding that supports the inclusion of these subjects in future COVID-19 diagnostic clinical trials and the FDA’s recommendation of serial antigen testing to improve antigen test performance.